A Study on Developing Pico Propeller Turbine for Low Head Micro Hydropower Plants in Nepal - Adhikari, Pradhumna; Budhathoki, Umesh; Timilsina, Shiva Raj; Manandhar, Saurav; Bajracharya, Tri Ratna (Journal of the Institute of Engineering, 2014)
Most of the turbines used in Nepal are medium or high head turbines. These types of turbines are efficient but limited for rivers and streams in the mountain and hilly region which have considerably high head. Low head turbines should be used in the plain region if energy is to be extracted from the water sources there. This helps in the rural electrification and decentralized units in community, reducing the cost of construction of national grid and also to its dependency, in already aggravated crisis situation. There are good turbine designs for medium to high heads but traditional designs for heads under about 5m (i.e. cross flow turbine and waterwheel) are slow running, requiring substantial speed increase to drive an AC generator. Propeller turbines have a higher running speed but the airfoil blades are normally too complicated for micro hydro installations. Therefore, the open volute propeller turbine with constant thickness blades was ventured as possible solution. Such type of propeller turbine is designed to operate at low inlet head and high suction head. This enables the exclusion of closed spiral casing. Also, the constant thickness blades enable the use of forging process instead of casting of complex airfoil blades. This leads to considerable reduction in manufacturing cost and complexity. A 1kW prototype was designed and scale down model of 185W was fabricated and tested. The runner consisted of five blades of 4mm thickness with camber and twist. The runaway speed of 1058 rpm was attained at design flow rate of 25 l/s. At full load the efficiency of model was found to be about 57%. Applying scaling effects the expected efficiency of the prototype was estimated to be about 60%. DOI: http://dx.doi.org/10.3126/jie.v9i1.10669 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 36–53